IGFBP2 Modulates Trophoblast Function and Epithelial–Mesenchymal Transition in Preeclampsia via the PI3K/AKT Signaling Pathway - Shengping Meng; Yanping Qin; Chunyan Lyu; Sumei Wang (Current Issues in Molecular Biology, 2025)
Background: Preeclampsia (PE) is a deadly obstetric complication in pregnant women leading to escalated rates of maternal and fetal mortality. Current research indicates that inadequate invasion of extravillous trophoblasts (EVTs) is a primary factor associated with the pathogenesis of PE. Insulin-like growth factor binding protein 2 (IGFBP2) plays a significant role in promoting cell migration, invasion, and angiogenesis. Researchers aim to investigate the clinical significance and elucidate the molecular mechanisms of IGFBP2 in the pathogenesis of preeclampsia. Methods: This study included 40 pregnant women categorized into 20 PE patients and 20 healthy controls. Expression levels of the mRNA were quantified using real-time quantitative polymerase chain reaction (qRT-PCR), and protein levels were assessed through Western blotting and immunofluorescence techniques. Moreover, the gain- and loss-of-function assays were conducted in human trophoblast cell line HTR-8/SVneo, and cellular models exhibiting overexpression and the knockdown of IGFBP2 were established. The proliferation, migration, and invasion of HTR-8/Svneo cells were determined using CCK8, wound-healing, and transwell assays, respectively. Results: The IGFBP2 was significantly downregulated, and the EMT was suppressed in the placental tissues of the PE patients. Functional experiments demonstrated that IGFBP2 enhanced the proliferation, invasion, and EMT of trophoblast cells activated through the PI3K/AKT signaling pathway. Conclusion: Our findings indicated that IGFBP2 enhances the proliferation, invasion, and EMT of trophoblast cells by activating the PI3K/AKT signaling pathway, serving as a potential therapeutic target in PE patients.